Activity of Antarctic fungi extracts against phytopathogenic bacteria - Purić, J. [UNESP]; Vieira, G. [UNESP]; Cavalca, L. B. [UNESP]; Sette, L. D. [UNESP]; Ferreira, H. [UNESP]; Vieira, M. L.C.; Sass, D. C. [UNESP] (Oxford University Press (OUP), 2018)
This study aims to obtain secondary metabolites extracts from filamentous fungi isolated from soil and marine sediments from Antarctic ecosystems and to assess its potential antibacterial activity on Xanthomonas euvesicatoria and Xanthomonas axonopodis pv. passiflorae (phytopathogenic bacteria causing diseases in pepper and tomato and passionfruit, respectively). Among the 66 crude intracellular and extracellular extracts obtained from fungi recovered from soil and 79 obtained from marine sediment samples, 25 showed the ability to prevent the growth of X. euvesicatoria in vitro and 28 showed the ability to prevent the growth of X. axonopodis pv. passiflorae in vitro. Intracellular and extracellular extracts from soil fungi inhibited around 97% of X. euvesicatoria and 98% of X. axonopodis pv. passiflorae at 2·1 mg ml−1. The average inhibition rates against X. euvesicatoria and X. axonopodis pv. passiflorae for intracellular and extracellular extracts from marine sediments fungi were around 96 and 97%, respectively, at 3·0 mg ml−1. Extracts containing secondary metabolites with antimicrobial activity against X. euvesicatoria and X. axonopodis pv. passiflorae were obtained, containing possible substitutes for the products currently used to control these phytopathogens. Significance and Impact of the Study: Micro-organisms from extreme ecosystems, such as the Antarctic ecosystem, need to survive in harsh conditions with low temperatures, low nutrients and high UV radiation. Micro-organisms adapt to these conditions evolving diverse biochemical and physiological adaptations essential for survival. All this makes these micro-organisms a rich source of novel natural products based on unique chemical scaffolds. Discovering novel bioactive compounds is essential because of the rise in antibiotic-resistant micro-organisms and the emergence of new infections. Fungi from Antarctic environments have been proven to produce bioactive secondary metabolites against various micro-organisms, but few studies have shown activity against Xanthomonas phytopathogens.
Keywords: antibacterial; passionfruit; phytopathogen; tomato; Xanthomonas